2020
DOI: 10.1002/art.41100
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pulmonary Hypertension Associated With Systemic Sclerosis in P‐Selectin Glycoprotein Ligand 1–Deficient Mice

Abstract: Objective Pulmonary arterial hypertension (PAH), one of the major complications of systemic sclerosis (SSc), is a rare disease with unknown etiopathogenesis and noncurative treatments. As mice deficient in P‐selectin glycoprotein ligand 1 (PSGL‐1) develop a spontaneous SSc‐like syndrome, we undertook this study to analyze whether they develop PAH and to examine the molecular mechanisms involved. Methods Doppler echocardiography was used to estimate pulmonary pressure, immunohistochemistry was used to assess va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Sustaining a more effector-like T cell response is vital for the immune system to control cancer, and PSGL-1 can affect the balance of inflammatory and suppressive cells. As mentioned previously, Selplg −/− mice with DSS-induced colitis show an increased effector T cell to Treg ratio in the colon, a trend that was also observed in the lungs of Selplg −/− mice ( 75 , 175 ). In an experimental autoimmune encephalomyelitis (EAE) model, PSGL-1 on Tregs was found to be necessary for suppression of the late stage T cell response ( 48 ).…”
Section: Role Of Psgl-1 In Diseasesupporting
confidence: 77%
See 1 more Smart Citation
“…Sustaining a more effector-like T cell response is vital for the immune system to control cancer, and PSGL-1 can affect the balance of inflammatory and suppressive cells. As mentioned previously, Selplg −/− mice with DSS-induced colitis show an increased effector T cell to Treg ratio in the colon, a trend that was also observed in the lungs of Selplg −/− mice ( 75 , 175 ). In an experimental autoimmune encephalomyelitis (EAE) model, PSGL-1 on Tregs was found to be necessary for suppression of the late stage T cell response ( 48 ).…”
Section: Role Of Psgl-1 In Diseasesupporting
confidence: 77%
“…Selplg −/− mice have been shown to develop a systemic sclerosis (SSc)-like syndrome. In these mice, the absence of PSGL-1 led to a notable decrease in Tregs in the lungs and an increase in IFN-γ-producing T cells and macrophages, highlighting the role of PSGL-1 in immunosuppression ( 175 ). Another autoimmunity study of SSc-like disease in Selplg −/− mice found increased serum levels of autoantigens, activated DC and CD4 + T effector cells in the skin, vascular damage, and increased mortality rates in mice due to loss of PSGL-1 ( 176 ).…”
Section: Role Of Psgl-1 In Diseasementioning
confidence: 92%
“…PSGL-1 regulates leukocyte activation, recruitment, and infiltration via binding to E-selectin and P-selectin, which play an important role in initiating inflammatory responses[ 5 ]. Knockdown of PSGL-1 effectively reduces the numbers of circulating neutrophils and monocytes, improves endothelial damage, and decreases blood pressure[ 6 ]. Blocking functional PSGL-1 reduces visceral adipose inflammation and ameliorates endothelial dysfunction in atherosclerosis[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of PSGL-1/P-selectin interactions in different animal models of acute inflammation has been well established (21)(22)(23)(24)(25)(26). However, in recent years, a new role in the preservation of immune homeostasis has been described for PSGL-1/P-selectin interaction (27)(28)(29)(30). In human monocyte-derived dendritic cells, interaction between P-selectin and PSGL-1 triggers a tolerogenic program characterized by the increase in IL-10, TGF-b; and IDO mRNA (30).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PSGL-1 knock-out mice (PSGL-1 −/− ) develop a systemic sclerosis (SSc)-like syndrome recapitulating the hallmarks of human disease: vascular damage, autoimmunity, and skin fibrosis (30). Interestingly, PSGL-1 −/− female mice also develop pulmonary hypertension associated with this scleroderma-like syndrome (27). In the case of P-selectin deficient mice (P-sel −/− ), lack of PSGL-1/P-selectin interaction results in a systemic lupus erythematosus (SLE)-like syndrome, characterized by the production of SLE-specific autoantibodies such as anti-dsDNA or anti-RNP, reduced dermal T effector/Treg ratio, and lung and renal involvement (28).…”
Section: Introductionmentioning
confidence: 99%